Improving hardiness among university students: A meta-analysis of intervention studies - Jianping, Gao; Zhihui, Zhu; Roslan, Samsilah; Zaremohzzabieh, Zeinab; Burhanuddin, Nur Aimi Nasuha; Geok, Soh Kim (Frontiers in Psychology, 2023)
Increasing the hardiness of students is a crucial objective in higher education. Universities and colleges have created a variety of interventions to improve students’ overall hardiness. In terms of the effects of such interventions, empirical research has shown inconclusive results. This meta-analysis applies 12 effect sizes from 12 independent empirical studies, with a total of 640 participants, to assess the overall impact of interventions on students' hardiness and to test for moderators, in light of the contradictory findings in prior work. The current meta-analysis calculates the standardized mean differences (SMD) of pre-post interventions. The level of study heterogeneity, represented by I2, was interpreted as small (I2 ≤ 25%), moderate (25% < I2 ≤ 50%), substantial (50% < I2 ≤ 75%), or considerable (I2 > 75%). Twelve studies met the inclusion criteria and were included in the meta-analysis. The results show that the interventions had a significant positive overall effect on students’ hardiness (g=0.998, k=12) and show significant heterogeneity among effect sizes. Among the interventions, cognitive-based intervention yielded the largest mean effect size (g=2.015, k=5). Furthermore, moderator analyses suggest that the effects of the interventions on students’ hardiness are moderated by respondent type, culture, intervention type, research design, years, and duration of intervention. We conclude that interventions that promote students’ hardiness are officious. Despite the low homogeneity of the results and limitations of this meta-analysis (e.g. a small number of included studies) which might have influenced the findings, the large fail-safe N suggests that these findings are robust. The study examined potential causes of heterogeneity and emphasized the importance of further research in this area.